Peningkatan Aktivitas dan Hasil Belajar Siswa pada Pembelajaran IPA Materi Gerak Benda Melalui Pendekatan Saintifik - FAQIH, NUR (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2019)
One of the main problems in learning is the low absorption of students. This can be seen from student learning outcomes which are still very concerning. This problem is also found in class III SDI. AN-NUR in science learning material Motion. In the initial data collection the authors found that from 38 students with KKM 75 there were 28 students (74%) not yet completed, and 10 students (26%) who achieved completeness. This is because the learning model used is still conventional (teacher centered). The purpose of this study was to improve the activities and learning outcomes of science materials Object movement in third grade students of SDI AN-NUR through a scientific approach. This type of research is a type of classroom action research (CAR). The subjects in this study were Class III students of SDI AN - NUR Surabaya Academic Year 2015/2016, with a total of 38 students, consisting of 11 men and 27 women. This study was conducted in two cycles with one meeting each cycle. The results showed that the application of the scientific approach obtained the completeness value of student learning outcomes which in the first cycle was 18 (47%), in the second cycle were 34 (89%) students. In addition, the results of the study indicate an increase in student activity in science subjects. Thus it can be concluded that the scientific approach can improve learning activitiesand learning outcomes.